What Do Gases in the Large Intestine Have to Do with Health? - Klaudia Pawełek; Patrycja Kinga Marta; Filip Maciej Huzarski; Gabriela Monika Ferfecka; Magdalena Rosa-Bończak; Agata Ossolińska; Weronika Kłosowicz; Oliver Carlton; Lucyna Stolarska; Natalia Morawiecka (Journal of Education, Health and Sport)
A healthy human gastrointestinal tract contains approximately 200 ml of gas, with an average daily elimination of 600 ml. Sources of intestinal gases include swallowing air and products of intestinal fermentation, primarily in the large intestine. The gases consist of nitrogen, oxygen, carbon dioxide, hydrogen, and methane, with carbon dioxide and hydrogen being the most abundant. The gut-brain axis, regulated by the nervous system and gut microbiota, influences intestinal motility, hormone secretion, and metabolic processes. Gut microorganisms produce short-chain fatty acids (SCFAs), which play a significant role in regulating energy homeostasis and enteroendocrine hormone secretion.